Distribution, expression of hexaploid wheat Fes1s and functional characterization of two TaFes1As in Arabidopsis - Lu, Yunze; Ha, Mingran; Li, Xinming; Wang, Junzhe; Mo, Ruirui; Zhang, Aihua (Frontiers in Plant Science, 2022)
Hexaploid wheat is a major food crop and is sensitive to heat stress. It is necessary to discover genes related to thermotolerance in wheat. Fes1s is a class of nucleotide exchange factor of heat shock protein 70s, proven to be participated in heat response in human, yeast, and Arabidopsis. However, little is known about Fes1s in hexaploid wheat. In this study, we identified nine Fes1s in hexaploid wheat (TaFes1s) and found that they present as three triads. A phylogenetic relationship analysis revealed that these Fes1s grouped into Fes1A, Fes1B and Fes1C subclades, and Fes1As and Fes1Bs were divergent in monocots, but possibly not in dicots. The sequences, gene structures and protein motifs of TaFes1s homoeologues within a triad were highly conserved. Through cis-elements analysis including heat shock elements, and miRNA targets prediction, we found that regulation of three TaFes1s homoeologues may be different, while the expression patterns of three homoeologues were similar. The expression levels of TaFes1As were higher than those of TaFes1Bs and TaFes1Cs, and based on these expressions, TaFes1As were chosen for functional characterization. Intriguingly, neither TaFes1A-5A nor TaFes1A-5D could not rescue the thermotolerance defect of Arabidopsis fes1a mutants at seedling stage, but in the transgenic plants seed germination was accelerated under normal and heat stress condition. The functional characterization indicated that roles of Fes1As would be different in Arabidopsis and hexaploid wheat, and function retention of TaFes1As may occur during wheat evolution. In conclusion, our study comprehensively characterized the distribution and expression of Fes1s in hexaploid wheat and found that two TaFes1As could accelerate seed germination under normal and heat stress condition.